PENGARUH DIFERENSIASI PRODUK DAN KUALITAS PELAYANAN TERHADAP TINGKAT PENJUALAN PT. AMORINDO MITRA SENTOSA MEDAN - Winny Ricky; Thomas Sumarsan Goh; Wily Julitawaty (JURNAL BISNIS KOLEGA, 2019)
Abstract. PT. Amorindo Mitra Sentosa Medan is a company engaged in the sale of shoes and bags. In its operations, there has been a decline in sales over the past 3 years due to a lack of differentiation of products offered by the company and service quality that has not been optimal so that it does not meet customer expectations. The formulation of the problem in this study is whether product differentiation and service quality affect the level of sales at PT. Amorindo Mitra Sentosa Medan.The method used in this study is a survey approach, this type of research is quantitative descriptive and the nature of this research is descriptive explanatory. The population in this study is permanent customers of PT. Amorindo Mitra Sentosa Medan as many as 64 stores. The sampling technique used in this study was saturated sampling and amounted to 64 stores. The method of data collection is done by a Likert scale. The data analysis model used to answer the hypothesis is multiple regression.The results also showed that partially product differentiation had an effect on sales volume and service quality had an effect on sales volume at PT. Amorindo Mitra Sentosa Medan. The results showed that simultaneously product differentiation and service quality had an effect on sales volume at PT. Amorindo Mitra Sentosa Medan. Â Keywords: Product Differentiation, Service Quality, Sales Volume